2019 19th International Working Conference on Source Code Analysis and Manipulation (SCAM) 2019
DOI: 10.1109/scam.2019.00034
|View full text |Cite
|
Sign up to set email alerts
|

Permission Issues in Open-Source Android Apps: An Exploratory Study

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 51 publications
(113 reference statements)
2
11
1
Order By: Relevance
“…In line with previous literature of mental health app reviews, we identified similar themes including the quality of information provided and language used, the presence of advertisements and customer service amongst other larger themes. Additionally, we also identified themes not exclusively reported for mental health apps including functionality ( 69 ), accessibility ( 70 ), and concerns about privacy and security ( 69 , 71 – 73 ). However, our analysis reveals theme frequencies and patterns which differ from previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…In line with previous literature of mental health app reviews, we identified similar themes including the quality of information provided and language used, the presence of advertisements and customer service amongst other larger themes. Additionally, we also identified themes not exclusively reported for mental health apps including functionality ( 69 ), accessibility ( 70 ), and concerns about privacy and security ( 69 , 71 – 73 ). However, our analysis reveals theme frequencies and patterns which differ from previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…Our approach is similar to [32,2,36,35] in terms of permission-related concerns, we dissimilar in terms of the dataset (including the size, features, and the number of permissions), using machine learning, and considering the categories'apps in their studies. In our present work, we expand on the existing research.…”
Section: B Permissions Based Studymentioning
confidence: 99%
“…In [32], the authors performed an empirical research of 574 open-source Android app GitHub repositories. They examined the incidence of four distinct sorts of permission-related concerns throughout the duration of the apps' lifetimes.…”
mentioning
confidence: 99%
“…The permissions system is considered a cornerstone component of the Android security model [8]. Consequently, the misuse of Android permissions is considered a major concern in the research community [9], [10] [11]. Several studies have been conducted on the evolution of Android permissions system [6], [7], [12], [5], [13].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Even though the security of Android permission system seems protected, the continues enhancements introduce various security issues and drawbacks [10], [11], [14]. Regardless of the Android version, the access enforcement in Android platform is subject to the API targeted level.…”
Section: B Permission-based Security Issuesmentioning
confidence: 99%